Operating reserve evaluation of aggregated air conditioners. (15th June 2017) - Hui, Hongxun; Ding, Yi; Liu, Weidong; Lin, You; Song, Yonghua
Highlights: A novel control strategy for the aggregation model of air conditioners (AC) is proposed. A series of indexes are proposed to evaluate the operating reserve performance provided by ACs. Operating reserve performance provided by both individual AC and aggregated ACs are analysed quantitatively. Operating reserve from demand-side can be dispatched by the system operator similar as conventional generating units. Abstract: The penetration of renewable energy sources (RES) in power system is increasing around the world. However, the severe intermittency and variability characteristics of RES make the operating reserve become more and more important for the electric power system to maintain balance between supply and demand. Moreover, the flexible loads, especially for air conditioners (AC), are growing so rapidly that they account for an increasingly large share in power consumption. With the development of information and communication technologies (ICT), ACs can be monitored and controlled remotely to provide operating reserve and respond actively when needed by the electric power system operation. In this paper, a novel control strategy for the aggregation model of ACs based on the thermal model of the room is proposed. By resetting the temperature of each AC, the operation state is adjusted temporarily without affecting customers' satisfaction. The operation characteristics of both individual AC and the aggregation model of ACs are analysed. Furthermore, several indexes are put forward to evaluate the operating reserve performance, including reserve capacity, response time, duration time and ramp rate. The effectiveness of the proposed control strategy is illustrated in the numerical studies.